# Recursion schemes, categorically! Traditional algebras deal with two things: 1. Building and parsing expressions 2. Evaluating expressions ## Building expressions Example of an expression: $$x^2 + 3 x + 4$$ When we parse such an expression we create an expression tree. We start with ![](https://i.imgur.com/SK0gWkS.png =160x) Expanding it recursively, we get ![](https://i.imgur.com/DT26CMb.png =400x) $3$ and $4$ are constants of type Double. Variables like x are strings. Plus and times are binary operators. scala sealed trait Expr case class Const(r: Double) extends Expr case class Var(a: String) extends Expr case class Times(l: Expr, r: Expr) extends Expr case class Plus(l: Expr, r: Expr) extends Expr  This is a recursive definition. We have non-recursive leaves, Const and Var, and recursive binary nodes Times and Plus. Our example is encoded as scala def expr: Expr = Plus(Times(Var("x"), Var("x")), Plus(Times(Const(3.0), Var("x")), Const(4.0)))))  which can be visualized as ![](https://i.imgur.com/dgapjHu.png =400x) ## Evaluating expressions An obvious choice to evaluate this expression is to turn it into a single Double value. We evaluate bottom up starting with leaves. A Const leaf can be evaluated to the value it contains. scala def eval(expr: Expr): Double = { expr match { case Const(x) => x ??? } }  For evaluation purposes, the variable node can be assigned any value of type Double, for instance x = 5. For simplicity, we'll assume that any other variable is initialized to zero scala def eval(expr: Expr): Double = { expr match { ??? case Var(s) => s match { case "x" => 5 case _ => 0 } ??? } }  In general, we can write many evaluators, or we can define an evaluator that is parameterized by the value of "x". To evaluate the nodes, we have to first recursively evaluate the children nodes producing values of the type Double scala def eval(expr: Expr): Double = { expr match { ??? case Times(l, r) => eval(l) * eval(r) case Plus(l, r) => eval(l) + eval(r) } }  The complete evaluator is then given by scala def eval(expr: Expr): Double = { expr match { case Const(x) => x case Var(s) => s match { case "x" => 5 case _ => 0 } case Times(l, r) => eval(l) * eval(r) case Plus(l, r) => eval(l) + eval(r) } }  But there are other choices for the result type of the evaluator, for instance, a string. A pretty printer is such an evaluator. The Const leaf is evaluated to a string representation of the Double it contains, a Var leaf to the name of the variable, and the nodes are evaluated recursively scala def pretty(expr: Expr): String = { expr match { case Const(x) => s"$x" case Var(s) => s case Times(l, r) => s"${pretty(l)} * ${pretty(r)}" case Plus(l, r) => s"${pretty(l)} + ${pretty(r)}" } }  The problem is that different evaluators mix the recursive logic with the logic of combining the results of evaluating the child trees. We are repeating the same boilerplate. We would like to factor these things out. ## Factorizing out the recursion When implementing an evaluator, we had to first choose the result type and then define a function of a particular type. We had a pair Double and eval and another pair String and pretty. There are two orthogonal concerns here: one is the recursive nature of evaluation, and the other is combining the results of the evaluation at every step. If the children are evaluated to Double, we add or multiply the numbers. If they are evaluated to String we concatenate them with the appropriate operator symbol between them. We'd like to create a data structure that would have placeholders for the results of the evaluation of the children. To do that, let's parameterize our Expr by the result type R scala sealed trait ExprF[R]  The leaves have no children scala sealed trait ExprF[R] case class ConstF[R](a: Double) extends ExprF[R] case class VarF[R](a: String) extends ExprF[R]  whereas the nodes do scala case class TimesF[R](l: R, r: R) extends ExprF[R] case class PlusF[R](l: R, r: R) extends ExprF[R]  In the original recursive definition the children were full-blown expression trees; here they are replaced by values of some general type R. R can stand for the result of the evaluation, or it could stand for the whole expression--as we'll see later when we define a fixed point. Altogether we get a data structure parameterized by R scala sealed trait ExprF[R] case class ConstF[R](a: Double) extends ExprF[R] case class VarF[R](a: String) extends ExprF[R] case class TimesF[R](l: R, r: R) extends ExprF[R] case class PlusF[R](l: R, r: R) extends ExprF[R]  With this definition we can implement our two evaluators as scala def evalF(expr: ExprF[Double]): Double = { expr match { case ConstF(x) => x case VarF(s) => s match { case "x" => 5 case _ => 0 } case TimesF(l, r) => l * r case PlusF(l, r) => l + r } }  scala def prettyF(expr: ExprF[String]): String = { expr match { case ConstF(x) => s"$x" case VarF(s) => s case TimesF(l, r) => l + " * " + r case Plus(l, r) => l + " + " + r } }  Notice that these implementations are no longer recursive. The idea is that such evaluators deal with a single level (either leaf or node) of an expression tree. They assume that child trees have already been evaluated, and they only combine those results. They only implement the *business logic* of the evaluator. But how do we use them to evaluate recursive expressions? For that we need a bit of category theory. # F-algebras We now have two evaluators, one producing a Double and another a String. We know that there are functions that can turn a Double into a String. Can we use such a function, for instance toString, to define a mapping of one evaluator to another? We can try two different ways of doing that: * We can take an ExprF Double, evaluate it using evalF and then apply our function toString to obtain a string. * Or we can take an ExprF Double, transform it to ExprF String, and then use the evaluator prettyF. In the latter, we have to transform ExprF Double to ExprF String. We can do this if ExprF is a functor. And, indeed, it is scala import cats._ import cats.implicits._ implicit val functorForExprF: Functor[ExprF] = new Functor[ExprF] { override def map[A, B](fa: ExprF[A])(f: A => B): ExprF[B] = fa match { case ConstF(x) => ConstF(x) case VarF(a) => VarF(a) case TimesF(l, r) => TimesF(f(l), f(r)) case PlusF(l, r) => PlusF(f(l), f(r)) } }  *Note: we are using [cats](https://typelevel.org/cats/typeclasses/functor.html) library instead of implementing our own functor.* We can now use map(_.toString) to turn ExprF Double to ExprF String. Unfortunately, the two ways of evaluating ExprF Double to a String produce different results. For instance, take PlusF(1.0, 2.0) * Apply evalF to it. You get 3.0, and then toString turns it to "3.0". * Apply map(_.toString) to it. You get PlusF("1.0", "2.0"). Then prettyF turns it to "1.0 + 2.0". Try it! scala val sum: ExprF[Double] = PlusF(1.0, 2.0) val s1 = evalF(sum).toString val s2 = prettyF(sum.map(_.toString))  We have to conclude that these two evaluators cannot be transformed into each other using toString in a consistent way. In other words, toString doesn't preserve "the structure" of our evaluator. On the other hand, some evaluators can be transformed into each other. Here's an evaluator which produces a pair (String, Double) scala def evalPair(expr: ExprF[(String, Double)]): (String, Double) = expr match { case ConstF(x) => ("Done", x) case VarF("x") => ("Done", 5) case VarF(_) => ("Done", 0) case TimesF((s, l), (_, r)) => (s, l * r) case PlusF((s, l), (_, r)) => (s, l + r) }  We'll use the following function to map one type to another scala def mkDone(x: Double): (String, Double) = ("Done", x)  We can check that the two ways of evaluating our test expression coincide scala v1 = mkDone(evalF(sum)) v2 = evalPair(sum.map(mkDone))  We'll say that mkDone preserves the structure of the evaluator. A combination of a type and an evaluator for a given functor F is called an *algebra* scala type Algebra[F[_], A] = F[A] => A  The type A is called the *carrier* of the algebra, and the evaluator is called the *structure map*. So far we've been concentrating on one such functor, ExprF, but algebras can be defined for any functor. We've seen three algebras for ExprF, with the carriers, respectively, Double, String and (String, Double) scala def evalF : Algebra[ExprF, Double] def prettyF : Algebra[ExprF, String] def evalPair: Algebra[ExprF, (String, Double)]  Functions between carriers that preserve the algebra structure are called *algebra morphisms*. We've seen one such algebra morphism, mkDone that maps the ExprF-algebra <Double, evalF> to <(String, Double), evalPair>. The function toString, on the other hand, is not an algebra morphism. The condition that has to be satisfied by an $F$-algebra morphism $(A, a) \to (B, b)$ corresponding to a function $f \colon A \to B$ is often represented by a *commuting diagram* ![](https://i.imgur.com/cEnJBOL.png =160x) where $F(f)$ is the lifting of $f$ by functor $F$ (which is done with map in Scala). We say that a diagram commutes if the two paths yield the same result. Here it is $$b \circ F(f) = f \circ a$$ In our example, $f$ was mkDone, $a$ was evalF, and $b$ was evalPair. Composition of functions is written as $f \circ g$ and read "f *after* g". In Scala we often invert the order and say g andThen f. By pasting two such diagrams, we can easily convince ourselves that a composition of two algebra morphisms $g \circ f$ is again an algebra morphism. The outer rectangle commutes because the two squares commute ![](https://i.imgur.com/B68FBBz.png =280x) The identity function is also an algebra morphism ![](https://i.imgur.com/KQ7zw35.png =160x) because $id \circ a = a \circ id$, and using the fact that a functor acting on identity is again an identity. Composition and identity are part of a definition of a *category* and, indeed, algebras and algebra morphisms for a given functor form a category (there is also the requirement of associativity of composition). The important part is that, in a category, we can define something called an *initial object*. Here, objects are algebras. An *initial algebra* is an algebra that has a unique outgoing algebra morphism to *any other algebra*. If we call the initial algebra <I, j>, with the carrier $I$ and the structure map $$j \colon F I \to I$$ then for any other algebra <A, a> we have a unique $m \colon I \to A$ such that the following diagram commutes ![](https://i.imgur.com/iD2Z4Yg.png =160x) This might seem unlikely, considering how hard it is to satisfy the commutation condition. But it turns out that our functor ExprF has an initial algebra. In fact, we've seen it already: its carrier type is the recursive data type Expr. Indeed, we can easily define an evaluator ExprF Expr => Expr scala def j: Algebra[ExprF, Expr] = { case ConstF(x) => Const(x) case VarF(s) => Var(s) case TimesF(l, r) => Times(l, r) case PlusF(l, r) => Plus(l, r) }  The key result that explains this is the *Lambek's Lemma*. It states that the structure map (the evaluator) of the initial algebra is an isomorphism. Indeed, if you look at our implementation of j, you see that it can be easily inverted. The proof of the Lambek's lemma is pretty straightforward and we leave it to the appendix. Since $j$ is an isomorphism, we can write $$F I \cong I$$ In other words, $I$ is a *fixed point* of $F$: the action of $F$ on $I$ gives us back the same $I$. This is how we can express the fixed point of a functor F in Scala scala case class Fix[F[_]](unfix: F[Fix[F]])  The isomorphism is witnessed by two functions, in and out. scala object Fix { def in[F[_]]: F[Fix[F]] => Fix[F] = ff => new Fix[F](ff) def out[F[_]]: Fix[F] => F[Fix[F]] = f => f.unfix }  Notice that in is the evaluator for the F-algebra with the carrier Fix[F], and out is its inverse. Fix[ExprF] is equivalent to our recursive data structure Expr. It contains exactly the same information. scala type Ex = Fix[ExprF]  We can define helper functions called *smart constructors* to help us build recursive expressions of the type Fix[ExprF] scala def v(s: String): Ex = Fix(VarF(s)) def num(d: Double): Ex = Fix(ConstF(d)) def mul(l: Ex, r: Ex): Ex = Fix(TimesF(l, r)) def add(l: Ex, r: Ex): Ex = Fix(PlusF(l, r))  Our original expression $x^2 + 3 x + 4$ can be written as scala val expr = add(mul(v("x"), v("x")), add(mul(num(3), v("x")), num(4)))  These smart constructors can be also used to implement a mapping from Expr to Ex. We'll implement the inverse mapping later using a catamorphism. ## Catamorphisms By definition of an initial object, there exists a unique mapping from the initial algebra to any other algebra ![](https://i.imgur.com/iD2Z4Yg.png =160x) Using Lambek's lemma, we can express the carrier of the initial algebra as a fixed point Fix F, with the evaluator in and its inverse out ![](https://i.imgur.com/CXkPRiG.png =260x) By following the arrows, this diagram allows us to express m, recursively, as a composition $$m = alg \circ F(m) \circ out$$ The unique function $m$ is called a *catamorphism* for a given algebra. This formula translates directly to code. scala def cata[F[_] : Functor, A](alg: Algebra[F, A]): Fix[F] => A = { ex => Fix.out[F].andThen(_.map(cata(alg))).andThen(alg)(ex) }  Let's analyze what happens when we apply a catamorphism to a particular expression scala val expr = add(mul(v("x"), v("x")), add(mul(num(3), v("x")), num(4)))  First, we apply out, which exposes the top level node scala def out: Fix[F] => F[Fix[F]]  In this case, expr was created by applying Fix to a PlusF node containing two expressions scala def add(l: Ex, r: Ex): Ex = Fix(PlusF(l, r))  Applying out to it exposes PlusF e e'. We then apply the catamorphism to this node's children using _.map(cata(alg)). This is where the recursion kicks in. But since the children are smaller than the original tree, the recursion is well founded--we are eventually bound to hit the leaves, at which point the recursion terminates (see the action of map on leaves). This recursive application reduces the children to values of the carrier type. We can then apply the evaluator to our top-level node and obtain the final value. So that's the idea: you evaluate the children and then combine the results within a node. The recipe for combining the results is the algebra. We are now ready to apply catamorphisms to the algebras we have previously defined. For instance, we can use our prettyF scala def prettyF: Algebra[ExprF, String] = { case ConstF(x) => s"$x" case VarF(s) => s case TimesF(l, r) => l + " * " + r case PlusF(l, r) => l + " + " + r }  to pretty print the expression scala val expr = add(mul(v("x"))(v("x"))) (add(mul(num(3))(v("x"))) (num(4)))  scala cata(prettyF).apply(expr)  As we mentioned before, the conversion from the fixed point form to Expr can also be done using a catamorphism scala val toExpr: Algebra[ExprF, Expr] = { case ConstF(x) => Const(x) case VarF(s) => Var(s) case TimesF(l, r) => Times(l, r) case PlusF(l, r) => Plus(l, r) } def mkExpr = cata(toExpr)  You can find the code [here](https://gist.github.com/oli-kitty/4e7d094eab28f57b8312c9d12f7403de) ### Appendix. Lambek's lemma Suppose that$\langle I, j \rangle$is the initial$F$-algebra with the structure map$j \colon F I \to I$. It means that for any other algebra$\langle A, a \rangle$there is a unique function$m \colon I \to A$such that the following diagram commutes ![](https://i.imgur.com/11Dt6gE.png =150x) It so happens that$\langle F I, F j \rangle$is also an$F$-algebra, because the lifting of$j$has the right type $$F j \colon F (F I) \to F I$$ There must, therefore, be a unique algebra morphism from$\langle I, j \rangle$to it making the following diagram commute ![](https://i.imgur.com/hnobm8b.png =165x) We could draw another diagram ![](https://i.imgur.com/KFCy3dP.png =165x) which trivially commutes, because the two paths are identical. We can paste the two diagrams together to form a larger commuting rectangle ![](https://i.imgur.com/bCtJc34.png =260x) The bottom of this diagram,$j \circ m$is therefore also an algebra morphism, but it's an algebra morphism from the initial algebra to the initial algebra. The initiality condition tells us that there can be only one such morphism, and we know that the identity function satisfies this condition. Therefore$j \circ m$must be the same as the identity $$j \circ m = id$$ We can now lift this equation to get $$F j \circ F m = id$$ (functor laws ensure that the lifting of a composition is a composition of liftings, and that the lifting of identity is an identity). But we have established earlier that this diagram commutes ![](https://i.imgur.com/hnobm8b.png =165x) This is only possible if$m \circ j = id$. This proves that$m$is both the left and right inverse of$j$and, therefore, that$j\$ is an isomorphism.